Common bean value chain actors share their feeling about TL projects in Tanzania - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
Apart from groundnut, Tropical Legumes I, II, and III also focused on common beans in Tanzania. In early April 2018, we visited Selian Agricultural Research Institute in Arusha, which is in the Northeast of Tanzania, and about 100 km from the Kenyan border. We also visited Mbeya, a town in the Southwest of Tanzania, just about 100 km from both Malawi and Zambia borders. Here, we found the first collaborator of Michael Kilango at Tanzania Agricultural Research Institute-Uyole who took us to meet different people in Mbeya and Mbozi areas. Apart from groundnut, Tropical Legumes I, II, and III also focused on common beans in Tanzania. In early April 2018, we visited Selian Agricultural Research Institute in Arusha, which is in the Northeast of Tanzania, and about 100 km from the Kenyan border. We also visited Mbeya, a town in the Southwest of Tanzania, just about 100 km from both Malawi and Zambia borders. Here, we found the first collaborator of Michael Kilango at Tanzania Agricultural Research Institute-Uyole who took us to meet different people in Mbeya and Mbozi areas.